PEMANFAATAN INFORMASI BERDASARKAN PORTERâS FIVE FORCES DALAM BISNIS FABRIKASI BAJA UNTUK MENDAPATKAN KEUNGGULAN BERSAING - Kusuma, Kristiawan Hengki (JURNAL DIMENSI UTAMA TEKNIK SIPIL, 2015)
Nowadays, steel fabricator has realized the importance of the use of information as a new tools to gain the competitive advantages with competitors. Unfortunely the use odf the information is still applied in an unconventional manner, the use of information are limited only to IT, without realizing actual use information has a lot of great potential if used optimally.The ârecklessâ use of information was not only less effective but also often lead to new problems. The result of data processed by ITâs, usually are not in line with the purpose to be achieved by company management due the differences in the interpretation of the concept, and as for the results of data processing can also cause misunderstanding between management.On this research will try the utilization of information by using Porterâs Five Forces as the tools to gain the competitive advantages. It will be explained also how to collect all information in business process that required in company and how to process this data to be competitive advantages for steel fabrication company.